THREE DIMENSIONAL COMPLEX SHAPES ANALYSIS FROM 3D LOCAL CURVATURE MEASUREMENTS. APPLICATION TO INTERMETALLIC PARTICLES IN ALUMINIUM ALLOY 5XXX - Parra-Denis, Estelle; Moulin, Nicolas; Jeulin, Dominique (Image Analysis and Stereology, 2011)
The studied material is a 5xxx aluminium alloys containing 2 types of intermetallic particles : Alx(Fe;Mn) and Mg2Si. It is usually used in car industry as reinforcement pieces or in packaging industry, such as bottle liquid box lid. Scanning electronic microscope coupled with EDX analysis shows complex shapes of intermetallic particles. The particle shape is obtained during the solidification of alloys. Particles fill vacant spaces between aluminium grains. Therefore final sheet properties depend on intermetallic particles shapes and notably on the matrix-particle interface properties. The goal of the present study is to classify intermetallic particles versus their shapes using local curvature information. The aluminium alloys sample is observed by X ray micro tomography performed at the ESRF. Three dimensional images are segmented, and intermetallic particles are identified in a data base. Each particle is stored as a set of voxels. The surface of each particle is meshed by a marching cubes triangular meshing with the software Amira©. A simplification of the surface is performed by an algorithm contracting the edges. Finally, principal curvatures: kmin and kmax are estimated by Amira© on each facet centre of the mesh. From the full intermetallic population, the bivariate distribution of kmin and kmax is estimated. The obtained graph kmin ¡kmax shows geometrical properties of interface portions of the surface of particles. A factorial correspondence analysis is performed to summarize the information on all intermetallic particles. In the obtained subspace, particles are classified into five shape families, in relation with their interface geometrical properties.